2015
DOI: 10.1021/ja511984q
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenophene Comonomer Comparison in Small Band Gap Diketopyrrolopyrrole-Based Conjugated Polymers for High-Performing Field-Effect Transistors and Organic Solar Cells

Abstract: The design, synthesis, and characterization of a series of diketopyrrolopyrrole-based copolymers with different chalcogenophene comonomers (thiophene, selenophene, and tellurophene) for use in field-effect transistors and organic photovoltaic devices are reported. The effect of the heteroatom substitution on the optical, electrochemical, and photovoltaic properties and charge carrier mobilities of these polymers is discussed. The results indicate that by increasing the size of the chalcogen atom (S < Se < Te),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
318
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(329 citation statements)
references
References 48 publications
(76 reference statements)
10
318
1
Order By: Relevance
“…= 866 nm) can be used to generate bulk heterojunction solar cells with PCE values in the range of 5.07.1%, with both inverted and conventional device architectures reported. 26 In related studies by Jo and co-workers, the isoindigotellurophene polymer 18 was prepared and shown to exhibit modest PCE values (1.1%) when blended with PC 61 BM ([6,6]-phenyl-C61-butyric acid methyl ester). 28 …”
Section: New Routes To Tellurium Heterocycles and Post-functionalizatmentioning
confidence: 99%
See 1 more Smart Citation
“…= 866 nm) can be used to generate bulk heterojunction solar cells with PCE values in the range of 5.07.1%, with both inverted and conventional device architectures reported. 26 In related studies by Jo and co-workers, the isoindigotellurophene polymer 18 was prepared and shown to exhibit modest PCE values (1.1%) when blended with PC 61 BM ([6,6]-phenyl-C61-butyric acid methyl ester). 28 …”
Section: New Routes To Tellurium Heterocycles and Post-functionalizatmentioning
confidence: 99%
“…23 The same group reported solar cells consisting of molecular donor molecules with capping benzotellurophene substituents, leading to elevated PCE values of up to 5.8%. 25 The use of 2,5-bis(trimethylstannyl)tellurophene (15) as a synthon to prepare conducting polymers via Stille coupling has been reported recently by both Ashraf (polymer 16) 26 and Choi (polymer 17).…”
Section: New Routes To Tellurium Heterocycles and Post-functionalizatmentioning
confidence: 99%
“…It is well known that large crystals show high stability and that the morphology stability of the active layer affects the device performance. [63][64][65][66][67][68] Aside from that, using a phase-separation strategy to achieve self-ecapsulation has also been found to be very effective. In 2008, Kang et al used this method and mixed TIPS-pentacene with two different molecular weight PαMS ( Figure 5).…”
Section: Api Effects On Stability Of Ofetsmentioning
confidence: 99%
“…For example, chalcogenophene-diketopyrrolopyrrole copolymers behave as active materials in polymer/fullerene bulk heterojunction solar cells with energy conversion efficiencies above 7%. [11] Using different chalcogenophenes in polymeric semiconductors is an efficient bandgap engineering strategy. [12] Herein, we report the systematic study of AIID-chalcogenophene polymers (PAIID), exploring the impact of structural variation on charge transport properties.…”
Section: Introductionmentioning
confidence: 99%